Pengaruh Trait Big Five Personality dan Dukungan Sosial Terhadap Flourishing Mahasiswa Menjalani Perkuliahan Selama Masa Pandemi (Universitas Muhammadiyah Metro, 2023)
Empirically, this study looks at the Effect of Big Five Personality Traits and Social Support on Flourishing Students Undergoing Lectures During the Pandemic Period. The population in this study were 150 students, and 150 students were the sample where the sample was taken using random sampling. Data collection techniques, namely questionnaires and documentation, were carried out by multiple regression, hypothesis testing, F test, and determination test. The results showed that the main effect of each of the Big Five dimensions of Personality and Social Support p: (1) a. There is a significant positive effect between Extraversion and Flourishing personality types as seen from the significance value where the coefficient tx2ay = 9.529 with p = 0.000, means p <0.05, (2) b. There is no significant positive effect on Agreeableness Flourishing, where the coefficient tx2by 1.165 with p=0.282, means p> 0.05, (3) c. There is a significant favourable influence between Counsicientiousness and flourishing personality types where the coefficient tx2cy = 10.099 with p = 0.000, means p <0.05, (4) d. There is no significant positive effect between Nerotic and Flourishing personality types, where the coefficient of tx2dy is 0.896 with p = 0.372, meaning p>0.05, (5) e. There is no significant positive effect between Openness to experience and flourishing personality types, where the tx2ey coefficient is 0.098 with p = 0.922, meaning p> 0.05. Social support has a significant positive effect on Flourishing where the value of the coefficient tx1y = 8.161 with p = 0.000 means p <0.05. For the Interaction effect, (1). a, there is a significant influence of social support and personality type a (Extraversion) simultaneously on Flourishing where the coefficient F = 45.410, with p = 0.000 means p < 0.050. (2) b. Social support and personality type b (Agreeableness) significantly affect where the coefficient F = 34.853, with p = 0.000 means p < 0.050. (3) c. There is a significant influence of social support and personality type c (Conscientiousness) simultaneously on Flourishing where the coefficient F = 78.855, with p = 0.000 means p < 0.050. (4) d. Social support and personality type d (Nerotic) significantly affect Flourishing where the coefficient F = 33,497, with p = 0.000 means p < 0.050. (5) e. There is a significant effect of social support and personality type e (Openness to experience) simultaneously on Flourishing where the coefficient F = 33.080, with p = 0.000 means p < 0.050. Of the Big Five Personality and Social Support variables, only the Counsicientiousness and Extraversion dimensions have the most significant determination coefficient values, where Counsicientiousness (R2) = 0.518 or 51.80%. In contrast, Extraversion (R2) = 0.382 or 38, 20% (2) Thus, it can be concluded that of the five dimensions of Big Five Personality, two dimensions have a significant influence, namely Counsicientiousness and Extraversion between Big Five Personality and Social support with Flourishing in the third-semester students of the law faculty of North Sumatra University in undergoing college during their tenure pandemic.